Comprehensive genomic profiling of head and neck squamous cell carcinoma reveals FGFR1 amplifications and tumour genomic alterations burden as prognostic biomarkers of survival. (March 2018) - Dubot, C.; Bernard, V.; Sablin, M.P.; Vacher, S.; Chemlali, W.; Schnitzler, A.; Pierron, G.; Ait Rais, K.; Bessoltane, N.; Jeannot, E.; Klijanienko, J.; Mariani, O.; et al.
Abstract: Background: We aimed at identifying deleterious genomic alterations from untreated head and neck squamous cell carcinoma (HNSCC) patients, and assessing their prognostic value. Patients and methods: We retrieved 122 HNSCC patients who underwent primary surgery. Targeted NGS was used to analyse a panel of 100 genes selected among the most frequently altered genes in HNSCC and potential therapeutic targets. We selected only deleterious (activating or inactivating) single nucleotide variations, and copy number variations for analysis. Univariate and multivariate analyses were performed to assess the prognostic value of altered genes. Results: A median of 2 (range: 0–10) genomic alterations per sample was observed. Most frequently altered genes involved the cell cycle pathway ( TP53 [60%], CCND1 [30%], CDKN2A [25%]), the PI3K/AKT/MTOR pathway ( PIK3CA [12%]), tyrosine kinase receptors ( EGFR [9%], FGFR1 [5%]) and cell differentiation ( FAT1 [7%], NOTCH1 [4%]). TP53 mutations ( p  = 0.003), CCND1 amplifications ( p  = 0.04), CDKN2A alterations ( p  = 0.02) and FGFR1 amplifications ( p  = 0.003), correlated with shorter overall survival (OS). The number of genomic alterations was significantly higher in the HPV-negative population ( p  = 0.029) and correlated with a shorter OS ( p  < 0.0001). Only TP53 mutation and FGFR1 amplification status remained statistically significant in the multivariate analysis. Conclusion: These results suggest that genomic alterations involving the cell cycle ( TP53, CCND1, CDKN2A ), as well as FGFR1 amplifications and tumour genomic alterations burden are prognostic biomarkers and might be therapeutic targets for patients with HNSCC. Highlights: Poor overall survival is observed in head and neck squamous cell carcinoma harbouring the following alterations. Genomic alterations involving the cell cycle ( TP53, CCND1, CDKN2A ). FGFR1 amplifications. High tumour genomic alterations burden.